Translation and translating in German studies : a festschrift in honour of Raleigh Whitinger - Plews, John L.; Spokiene, Diana; Whitinger, Raleigh, 1944- (WCGS German studies series., 2016)
"These essays in honour of Raleigh Whitinger examine perspectives on translation and German Studies. Specifically, they explore processes of identity formation, gendered representations, visual and textual meditations, and teaching and learning practices."--